Prevalence, genetic diversity and recombination of species G enteroviruses infecting pigs in Vietnam. - Van Dung, N; Anh, P; Van Cuong, N; Hoa, N; Carrique-Mas, J; Hien, V; Campbell, J; Baker, S; Farrar, J; Woolhouse, M; Bryant, J; Simmonds, P (2014)
Picornaviruses infecting pigs, described for many years as 'porcine enteroviruses', have recently been recognized as distinct viruses within three distinct genera (Teschovirus, Sapelovirus and Enterovirus). To better characterize the epidemiology and genetic diversity of members of the Enterovirus genus, faecal samples from pigs from four provinces in Vietnam were screened by PCR using conserved enterovirus (EV)-specific primers from the 5' untranslated region (5' UTR). High rates of infection were recorded in pigs on all farms, with detection frequencies of approximately 90% in recently weaned pigs but declining to 40% in those aged over 1 year. No differences in EV detection rates were observed between pigs with and without diarrhoea [74% (n = 70) compared with 72% (n = 128)]. Genetic analysis of consensus VP4/VP2 and VP1 sequences amplified from a subset of EV-infected pigs identified species G EVs in all samples. Among these, VP1 sequence comparisons identified six type 1 and seven type 6 variants, while four further VP1 sequences failed to group with any previously identified EV-G types. These have now been formally assigned as EV-G types 8-11 by the Picornavirus Study Group. Comparison of VP1, VP4/VP2, 3D(pol) and 5' UTRs of study samples and those available on public databases showed frequent, bootstrap-supported differences in their phylogenies indicative of extensive within-species recombination between genome regions. In summary, we identified extremely high frequencies of infection with EV-G in pigs in Vietnam, substantial genetic diversity and recombination within the species, and evidence for a much larger number of circulating EV-G types than currently described.